How the R&S process in Webhelp’s Contact Centre impacts CSAs’ turnover intention: A business process outsourcing case study - Sabino, Beatriz Prazeres (2022)
The Contact Center Industry encompasses a high rate of turnover among contact center agents. By investigating the turnover phenomenon, this study aims to identify the practices and procedures of the Recruitment and Selection Process, as well as its quality. Together, it seeks to demystify how the process is conducted, by recruiters, under constant time pressures to clients, who are committed to outsource their services. By approaching recruiters, responsible for delivering/hiring potential profiles, it is necessary to also comprehend the relationship of recruitment coordinators, who assume functions as team leaders, on team’s proper function. Our study proved what was initially desired, therefore the quality of the recruitment and selection process has indeed, impact in the turnover intention of customer service agents.